Knowledge and The Level of Anxiety Towards The Willingness of theElderly to Receive the Covid-19 - Lisnawati, Lisnawati; Yusnayanti, Cici; Helty, Helty (Nursing Genius Journal, 2024)
The willingness of the elderly to receive the Covid-19 vaccine is currently a problem because some elderly people refuse to vaccinate. This happened because of the spread of hoax news in various media regarding the side effects of vaccines and there was some information regarding people who died after being vaccinated and there were some people who did not believe in the existence of the Covid-19 virus, of course this was influenced by a lack of knowledge and the level of finance. This study aims to determine the relationship between knowledge and anxiety levels on the willingness of elderly people to receive the Covid-19 vaccine in the Lepo-Lepo Health Care Center in Kendari City.         This type of research is quantitative with a cross sectional approach. The research sampling technique used a cluster random sampling technique, totaling 92 respondents. The data analysis method uses the chi square test and gamma test. The results of the knowledge statistical test show that x2 count = 67.663 > x2 table = 3.8415 and the anxiety level test results are p = 0.000. The results of this study show that there is a relationship between knowledge and anxiety levels regarding the health of elderly people receiving the Covid-19 vaccine. It is hoped that Puskesmas health workers can increase the knowledge of the elderly regarding the Covid-19 vaccine and can overcome the problem of anxiety levels felt by the elderly.